Strong enhancement of double Auger decay following plasmon excitation in C60 - Korica, Sanja Lj.; Reinkoester, Axel; Becker, Uwe (Vojnotehnički glasnik / Military Technical Courier, 2018)
One of the important characteristics of the C60 molecule is the collective response of its valence electron cloud to the electromagnetic radiation. This collective behavior gives rise to the occurrence of the giant dipole resonance (so called surface plasmon) in the absorption spectrum centered around 20 eV, which has also been analyzed theoretically by various authors. Concerning photoelectron emission, plasmonic excitation is characterized by a particular intensity behavior near the threshold. We present here a new series of the K-shell photoelectron spectra with particular emphasis on the qualitative analysis of all ionization with excitation and double ionization processes. Our measurements of the C60 plasmon excitation follow the so-called Thomas-Derrah law and are in good agreement with the corresponding behavior of satellite excitations in atoms such as neon.